GAMBARAN TINGKAT PENGETAHUAN SISWA KELAS XI TERHADAP BAHAYA PENYALAHGUNAAN OBAT TRAMADOL DI SMK “X” DI KABUPATEN KUNINGAN - Imas Maesaroh; Retina Aghistni Rahmawati (Publikasi Penelitian Terapan dan Kebijakan, 2018)
Tramadol is one of the drugs that is often misused by students or adolescents. Tramadol belongs to the peripheral analgesic group as a pain reliever and is obtained by prescription. Tramadol has an euphoria ef ect and causes dependence. One of the causes of drug abuse is lack of knowledge. This research was conducted with the aim to know the level of knowledge of class XI students against the dangers of drug abuse Tramadol in one of Vocational High School in Kuningan District. The research design used was descriptive quantitative research, with sampling using purposive sampling technique. Data collection was done by using questionnaire instrument. Of the 96 respondents, the average percentage of Students' Level of Class XI Knowledge on the Danger of Tramadol Drug Abuse in SMK "X" in Kuningan District is 76.61% of respondents’know' and 23.39% of respondent ‘ do not know'.From the result of data collection obtained the conclusion about the level of knowledge students class XI against the danger of Tramadol drug abuse in SMK “X” in Kuningan Regency be categorized good based the level of knowledge categories by Arikunto (2006) with the average result percentage in the amount of 76,61%. The result of hypothesis test showed revenue H0, it means the the average score of respondent ≥ 8.